2014
DOI: 10.1097/cin.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mining Techniques in Constructing a Traditional Chinese-Language Nursing Recording System

Abstract: In 2009, the Department of Health, part of Taiwan's Executive Yuan, announced the advent of electronic medical records to reduce medical expenses and facilitate the international exchange of medical record information. An information technology platform for nursing records in medical institutions was then quickly established, which improved nursing information systems and electronic databases. The purpose of the present study was to explore the usability of the data mining techniques to enhance completeness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The goal of DM is to access information for further analysis and potential decision making. 12,13 Text mining is a more comprehensive process than DM in which there is mining of unknown and obscure parts of information from structured and semistructured text. Although very similar, there are elements of a priori algorithms and association rules that form a basis for text mining.…”
Section: Generating New Knowledge For Decision Makingmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of DM is to access information for further analysis and potential decision making. 12,13 Text mining is a more comprehensive process than DM in which there is mining of unknown and obscure parts of information from structured and semistructured text. Although very similar, there are elements of a priori algorithms and association rules that form a basis for text mining.…”
Section: Generating New Knowledge For Decision Makingmentioning
confidence: 99%
“…12 Both involve accessing and extracting information from a large volume of documents. DM is the process in which useful knowledge and information is obtained from data banks.…”
Section: Generating New Knowledge For Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their process of assessment was complex and time consuming. Text mining provides information search, association, prediction, analysis, management, and decision-making support for a rapid and accurate analysis of unstructured text (Han et al, 2011; Liao et al, 2014; SAS Resource Center, 2014). This study employed SAS Text Miner to conduct text mining on electronic nursing records, identified the information hidden in the NFEs, and determined a method for auditing the quality of electronic nursing records.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on electronic nursing records have focused mostly on the evaluation of the developed system or on the degree of user satisfaction (Chang et al, 2013; Liao, Chu, & Chu, 2014; Wang et al, 2011). Few studies have investigated the quality of computerized nursing records.…”
Section: Introductionmentioning
confidence: 99%